Sling Versus No Sling After Superior Rotator Cuff Repair: A Propensity Score Matched, Longitudinal, Observational Study at Mid-Term Follow-up - Alexandre Lädermann; Patrick J. Denard; Philippe Collin; Xue Ling Chuong; Alberto Guizzi; Jeanni Zbinden; Hugo Bothorel (The Hive)
Background: Patients who underwent arthroscopic rotator cuff repair are often required to wear a sling after surgery despite the known adverse effects of immobilization with the intention to protect the cuff repair. Short-term results have proved to have good clinical outcomes even without a sling.